Issues in antifungal stewardship: an opportunity that should not be lost. (19th December 2016) - Wattal, Chand; Chakrabarti, Arunaloke; Oberoi, Jaswinder Kaur; Donnelly, J. Peter; Barnes, Rosemary A.; Sherwal, B. L.; Goel, Neeraj; Saxena, Sonal; Varghese, George M.; Soman, Rajeev; Loomba, Poonam; Tarai, Bansidhar; et al.
Abstract : Many countries have observed an increase in the incidence of invasive fungal infections (IFIs) over the past two decades with emergence of new risk factors and isolation of new fungal pathogens. Early diagnosis and appropriate antifungal treatment remain the cornerstones of successful outcomes. However, due to non-specific clinical presentations and limited availability of rapid diagnostic tests, in more than half of cases antifungal treatment is inappropriate. As a result, the emergence of antifungal resistance both in yeasts and mycelial fungi is becoming increasingly common. The Delhi Chapter of the Indian Association of Medical Microbiologists (IAMM-DC) organized a 1 day workshop in collaboration with BSAC on 10 December 2015 in New Delhi to design a road map towards the development of a robust antifungal stewardship programme in the context of conditions in India. The workshop aimed at developing a road map for optimizing better outcomes in patients with IFIs while minimizing unintended consequences of antifungal use, ultimately leading to reduced healthcare costs and prevention development of resistance to antifungals. The workshop was a conclave of all stakeholders, eminent experts from India and the UK, including clinical microbiologists, critical care specialists and infectious disease physicians. Various issues in managing IFIs were discussed, including epidemiology, diagnostic and therapeutic algorithms in different healthcare settings. At the end of the deliberations, a consensus opinion and key messages were formulated, outlining a step-by-step approach to tackling the growing incidence of IFIs and antifungal resistance, particularly in the Indian scenario.